DEVELOPMENT OF INTERACTIVE MEDIA BASED ON AUTOPLAY STUDIO FOR LEARNING MUFRODAT ARABIC - Aris Widada; Wiji Khayati; Lustia Bekti Rohayati (The University of Kuningan, 2021)
A challenge as well as a new breakthrough for Arabic language teachers to change the mindset that Arabic lessons are easy lessons to learn. One of them is by implementing learning media based on Autoplay Studio in Arabic language learning. The learning process by utilizing this media is not only fun, interactive but also challenging because it will have an effect on increasing the competence of students and the creativity of educators. Arabic learning at the SMP/MTs level is directed at mastering language skills (maharah al-lughah), which includes 4 skills including: 1). listening (maharah al-istima '); 2). speaking (maharah al-kalam), 3). reading (maharah al-qiraah), and 4). writing (maharah al-kitabah). These 4 skills cannot be achieved without having skills in good vocabulary mastery, because the quality of a person's language skills depends on the level of proficiency and the amount of vocabulary he has. This study uses the Research and Development (RD) Borg and Gall model. Sources of data in this study obtained by means of interview techniques, observation, and documentation. The results of this study are that teachers and students want the development of interactive multimedia-based learning media based on Autoplay Studio for Arabic vocabulary mastery for class VIII. The results of the assessment can be seen that the value of the overall media feasibility aspect is with an average value of 84.5 which means this media is in the score range of 81-100 reaching a scale of 5 with a very good category (very decent). Thus, it can be concluded that the interactive media based on Autoplay Studio that was developed is very suitable for use by class VIII students at SMP Muhammadiyah Imogiri.